(3Gdbhd aj Ndb GdEfSGf heeG Ndb heG QcH ajgs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd Mfjf Hf ESMGb GdeJWHH bGd YHO GdefYe Cfg hLO ai GdJhQGI UaI BOe Mjf Ndbg Gddg YR hLd s
(3BNQgG (B:s
(3hbaI cGJH jfJgi GdehLhO efg Hbhdg (B: (3hGYde Cf GdHdZe jcKQ ai KdGKI CTgQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP eMeO Gdefhfi HGdQHGW ef GdecJHGJ GdNGUI s
Keywords: (3GdWHs